Ethnic Capital and Class Reproduction: Comparing the Impact of Socio-Economic Status on Children's Educational Attainment Across Ethno-Religious Groups in Israel. Issue 3 (4th May 2021) - Miaari, Sami H.; Khattab, Nabil; Kraus, Vered; Yonay, Yuval P.
Abstract: This article investigates the relationships between ethnicity, class, and prospects of educational success. For this purpose, we compared the effects of family socio-economic characteristics on children's educational attainment in four ethno-religious groups in Israel (Muslim, Christian, and Druze Palestinians; Jews). Information from the 1995 census on the households with at least one child born in the cohort of 1975-1985 is matched with Ministry of Education records on all those who achieved matriculation certificates and academic degrees between 1995 and 2012. The results show that the educational outcomes of Christian and Druze children are less dependent on their family characteristics compared to Muslim and Jewish children. We suggest that the disadvantage of Palestinian schools in a Jewish-dominated state is offset by the tougher competition Jewish children from disadvantaged strata face in schools attended by those from affluent strata. Family background is more important for academic degrees than for the matriculation certificate. Furthermore, the education and occupation of mothers and fathers both have an equally important impact on child outcomes.